2019
DOI: 10.7759/cureus.5812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mitral Apparatus Blood Cyst: A Case Report and Review of Literature

Abstract: Intracardiac blood cysts (ICBC) are cardiac pseudoneoplasm commonly seen in infants below two months of age. ICBC typically resolve spontaneously; however, they can sometimes persist in adults and can cause detrimental consequences. A 47-year-old female presented to our facility with complaints of chest pain and was found to have an incidental subvalvular chordal mitral apparatus echolucent mass on transthoracic echocardiogram (TTE). A stress echocardiography was performed, which revealed transient left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Most authors suggest a conservative approach in asymptomatic patients with minor cysts. 3,10,11 In their opinion, surgical resection should be considered if symptoms occur or if the cysts lead to any cardiac dysfunction. Paşaoglu et al suggested surgical removal of cardiac blood cysts at the time of diagnosis, even if the patient is asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors suggest a conservative approach in asymptomatic patients with minor cysts. 3,10,11 In their opinion, surgical resection should be considered if symptoms occur or if the cysts lead to any cardiac dysfunction. Paşaoglu et al suggested surgical removal of cardiac blood cysts at the time of diagnosis, even if the patient is asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…9 They are often asymptomatic but few cases resulting in embolization and valvular dysfunctions have been reported. [10][11] Blood cysts involving heart valves were fi rst reported by Elsässer in 1844. 12 These cysts are usually blood-fi lled nodules measuring 1-2 mm, which are commonly associated with the atrioventricular valves, but they have also been reported as attached to the semilunar valves.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiogram seems more accurate than CT scan, but false negatives can occur when masses are located in the left ventricle due to difficulty for visualizing the ventricular apex [14]. In the compilation of cases by Dencker, only 2 out of 11 cases had a cardiac MRI for supporting the diagnosis [6]; nevertheless, this modality has been relevant for confirming (rather than discarding) the echocardiographic finding [1,8,15]. Lamentably, there are still administrative barriers that impede access to advance image modalities in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no treatment guidelines for blood cysts because of the low incidence, but the majority of symptomatic patients have undergone surgery for ruling out malignancy and preventing stroke [16]. β-blocking, antiaggregation, or anticoagulation remain controversial [15]. The prognosis is benign as congenital cysts tend to resolve spontaneously, but in fewer cases, valvular disease or obstruction of the ventricular outflow tracts can be present [9].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms related to the presence of MV BCs, in the absence of any other intracardiac abnormality, included predominantly palpitations, chest discomfort and exertional dyspnea. In 3 patients BCs caused severe left ventricular outflow tract (LVOT) obstruction 5,11,50 , 2 patients presented with hemiparesis 4,43 , 2 with syncopal episodes 32,50 , 2 had a stroke 15,18 , 2 a myocardial infarction 9,21 and in one the BC caused severe MV regurgitation 23 . Except for the first 2 BCs cases described, diagnosed either by cineangiography 3 or M-mode echocardiogram 5 , in all other cases transthoracic 2-D echo was used for evidencing the presence of a MV mass (Fig.…”
Section: )mentioning
confidence: 99%